IMPLEMENTASI PROGRAM ECONOMIC EMPOWERMENT OF WOMEN THROUGH CLIMATE-SMART AGRICULTURE OLEH UN WOMEN DALAM MENGATASI KRISIS EKONOMI DI KENYA - Putri, Nadia Zafira; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Women in Kenya face severe economic challenges due to gender inequality and the impacts of climate change that threaten the agricultural sector, particularly in climate-vulnerable regions such as Kitui County. These conditions heighten the vulnerability of small-scale women farmers and underscore the need for international organizations to strengthen their economic resilience. This study employs Clive Archer’s International Organization Theory and the Liberal Institutionalism perspective to analyze the role of UN Women in the Economic Empowerment of Women through Climate-Smart Agriculture program in Kenya. The research adopts a qualitative literature-based method through analysis of official reports, policy documents, and academic sources. The findings demonstrate that UN Women effectively functions as an independent actor that enhances multilateral cooperation and promotes women’s economic empowerment through climate-smart agricultural practices. The program has improved women’s adaptive capacity, income levels, and participation in sustainable development across Kenya. These results highlight the importance of gender-responsive international cooperation in addressing the economic and climate crises affecting women in vulnerable communities. Keywords: UN Women, Women’s Empowerment, Climate-Smart Agriculture, Liberal Institutionalism.